Tailoring the Electromagnetically Induced Transparency and Absorbance in Coupled Fano-Lorentzian Metasurfaces: A Classical Analog of a Four-Level Tripod Quantum System - Xu, Ningning (2017)
Absorbance spectra of a near-field coupled Fano-Lorentzian metasurfaces are explored. A strong absorption window develops from the transparency background by coupling a LC resonance to the electromagnetically induced transparency band. This classical behavior can be analoged to a quantum four-level tripod system, where the interference between a bright and two dark modes gives rise to this observation.